Peran Media Komunikasi Digital dalam Mendukung Negosiasi Bisnis di Era Hybrid Work - Manda Putra Hutabarat; Suwandi Suwandi (Kajian Ekonomi dan Akuntansi Terapan, 2025)
The hybrid work era, which combines remote work with face-to-face work, has brought about new challenges and opportunities in business communication, particularly in the negotiation process. This study aims to analyze the role of digital communication media in supporting the effectiveness of business negotiations. Using a descriptive qualitative approach, data was collected through in-depth interviews with several professionals from various industrial sectors who are active in online negotiation activities. The results indicate that digital communication media such as Zoom, Microsoft Teams, and WhatsApp play a crucial role in enhancing time efficiency, flexibility, and the speed of information exchange. However, limitations in nonverbal expression and the risk of miscommunication remain significant challenges. This study suggests adopting adaptive digital communication strategies, including virtual communication training and the use of a combination of synchronous and asynchronous media to achieve optimal negotiation outcomes.